2023
DOI: 10.1111/oik.09700
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of how parasites affect host consumption rates

Abstract: Parasites are known to mediate trophic interactions and can, for example, modify how consumers acquire resources. These modifications of host feeding behaviour can be imposed through three interconnected mechanisms affecting: 1) host food acquisition, 2) host food digestion or 3) host energy budgets. As a result, infected hosts may consume more, less or the same amount of food compared to their uninfected conspecifics. It is commonly assumed that infected hosts have lower consumption rates than uninfected host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…As a response to offsetting the cost of infection, host species may change behavior by increasing their foraging activity which can ultimately result advantageous to the host and the parasite ( Weinersmith & Earley, 2016 ). While a recent meta-analysis showed that parasite-infected hosts consume on average 25% less food than uninfected individuals, the study showed great variability among taxa with multiple examples of the opposite pattern ( Mrugała, Wolinska & Jeschke, 2023 ). For instance, parasite-infected rusty crayfish consume more macrophytes and macroinvertebrates than uninfected ones likely due to increased feeding behavior boldness induced by infection ( Reisinger & Lodge, 2016 ).…”
Section: Discussionmentioning
confidence: 86%
“…As a response to offsetting the cost of infection, host species may change behavior by increasing their foraging activity which can ultimately result advantageous to the host and the parasite ( Weinersmith & Earley, 2016 ). While a recent meta-analysis showed that parasite-infected hosts consume on average 25% less food than uninfected individuals, the study showed great variability among taxa with multiple examples of the opposite pattern ( Mrugała, Wolinska & Jeschke, 2023 ). For instance, parasite-infected rusty crayfish consume more macrophytes and macroinvertebrates than uninfected ones likely due to increased feeding behavior boldness induced by infection ( Reisinger & Lodge, 2016 ).…”
Section: Discussionmentioning
confidence: 86%